Tumors of unknown origin - Doassans, Carlos; Abelleira, Alfredo; Pressa, Carlos (Cirugía del Uruguay, 1990)
The experience ot diagnostic and therapeutic difficulties reiterated in conjunction with patients exhibiting a clinical history similar to that reported tormerly; this situation led the authors to undertake the revision of the tapie and its curren/ status.